Adaptive metamodel-based analytical target cascading for natural gas hydrates coring tool design optimization. Issue 7 (3rd July 2022) - Zheng, Jun; Lu, Chunhua; Li, Zilong; Jiang, Guosheng; Zhao, Huibin
Abstract : Design optimization and performance analysis of natural gas hydrates (NGH) coring tool is a complex engineering system that involves several disciplines, such as structural, hydraulics, thermology and mechanism kinematics. An adaptive metamodel-based analytical target cascading (A-ATC) method is developed to efficiently deal with the NGH coring tool design problem. The NGH coring tool design problem is decomposed into three subsystems through the proposed A-ATC approach; namely, the core tube subsystem, ball valve mechanics subsystem and hydraulic subsystem. Moreover, a parameterized lower confidence bounding (PLCB) scheme-based adaptive metamodel is introduced into A-ATC to replace the analysis module to alleviate the intensive computational burden. Optimization results of the NGH tool are compared with those of kriging-based ATC. The effectiveness of PLCB is investigated through comparisons with other commonly used infill strategies. The results show that the proposed PLCB-based A-ATC method is more appropriate for the NGH coring tool design optimization problem.